REVIEWING PESANTREN REGULATION IN INDONESIA: A TRANSCENDENT TAXONOMY PERSPECTIVE - Islamy, Athoillah; Zulihi; M. Syukri Nawir (STIT PRINGSEWU, 2024)
The role of the government and Islamic educational institutions in responding to social problems and the natural environment in Indonesia is urgent. In this context, Pesantren as part of Islamic education institutions in Indonesia is also expected to contribute greatly in overcoming these problems. Through a normative-philosophical approach, this qualitative study aims to identify the taxonomic form of Islamic education in regulations related to the orientation of organizing Islamic boarding schools in Indonesia. The primary data of this study is the document of Law No.18/2019 on Pesantren. The concept of transcendent taxonomy formulated by Ah. Zakki Fuad became the foundation of the perspective. Data collection using documentation techniques, and data analysis includes reduction, presentation, and verification. This study confirms the existence of theocentric (ilahiyat) and anthropocentric (insaniyat) dimensions as a transcendent taxonomy in regulations related to the orientation of Pesantren education. The theocentric dimension can be seen in the formation and strengthening of students who are faithful and pious. Then, the anthropocentric dimension can be seen in the formation of students who are knowledgeable, humanist, tolerant, moderate, and nationalist. This study confirms that the cosmocentric (kawniyat) dimension as part of the transcendent taxonomy is explicitly-normatively not yet included in the regulations related to the orientation of the Pesantren implementation in Indonesia. Therefore, it is important for the Indonesian government to pay further attention to include the cosmocentric dimension in the Pesantren regulation.